Innovative Moments and Change in Emotion-Focused Therapy: The Case of Lisa - Gonçalves, Miguel M. (2010)
This article presents an intensive case analysis of a good outcome case of emotion-focused therapy – the case of Lisa – using the Innovative Moments Coding System (IMCS). The IMCS, influenced by White’s narrative therapy, conceptualizes narrative change as resulting from the elaboration and expansion of narrative exceptions or unique outcomes to a client’s core problematic self-narrative. The IMCS identifies and tracks the occurrence of 5 different types of narrative change: action, reflection, protest, re-conceptualization, and performing change. This is the first attempt to use the IMCS with cases outside the narrative tradition. We discuss the results, emphasizing the commonalities and major differences between this case and other good outcome cases.